2023
DOI: 10.1007/s40618-023-02046-y
|View full text |Cite
|
Sign up to set email alerts
|

Retinal sensitivity and gaze fixation evaluated by microperimetry in subjects with type 2 diabetes: two independent parameters that explore different neuronal circuits

Abstract: Background and aims Retinal sensitivity (RS) and gaze fixation (GF) assessed by retinal microperimetry are useful and complementary tools for identifying mild cognitive impairment (MCI) in patients with type 2 diabetes (T2D). The hypothesis is that RS and GF examine different neural circuits: RS depends only on the visual pathway while GF reflects white matter complex connectivity networks. The aim of the study is to shed light to this issue by examining the relationship of these two parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…15,16 Fixation stability contributes to the complex network of white matter, superior colliculus, parietal, and frontal cortex, while macular sensitivity depends on the conduction of various links in the visual pathway. 17 Zhu et al 18 have found a significant correlation between mean sensitivity and HbA1c in patients with DR, and time in range (the percentage of time that the target glucose is in the range of 3.9–10.0 mmol/L over 24 hours, as one of the markers of continuous blood glucose testing) of glucose was significant positively correlated with mean sensitivity. However, in our study, there was no correlation between mean sensitivity and HbA1c, and duration of DM.…”
Section: Discussionmentioning
confidence: 95%
“…15,16 Fixation stability contributes to the complex network of white matter, superior colliculus, parietal, and frontal cortex, while macular sensitivity depends on the conduction of various links in the visual pathway. 17 Zhu et al 18 have found a significant correlation between mean sensitivity and HbA1c in patients with DR, and time in range (the percentage of time that the target glucose is in the range of 3.9–10.0 mmol/L over 24 hours, as one of the markers of continuous blood glucose testing) of glucose was significant positively correlated with mean sensitivity. However, in our study, there was no correlation between mean sensitivity and HbA1c, and duration of DM.…”
Section: Discussionmentioning
confidence: 95%